(untitled) (Global Journal of Human-Social Science, 2016)
All the sociological literature points to the Frankfurt School Theorists using Marx (for Alienated Labor) and Freud (for psychoanalysis) in constructing Critical Theory, (in an effort to explain the inhuman treatment of humanity by the German fascists). This original effort suggests that the foundational theorists (FTCT) of Critical Theory (Adorno, Fromm, Marcuse and Horkheimer) were also profoundly influenced by the Buddhist philosopher Nāgārjuna’s major thematic focus is sunyata or "emptiness," (one of the key Buddhist doctrines).